Digital Business Development Strategy in Samalewa Business Recycled Iron Craftin Sumbawa Regency - Alvin Juniansyah; Diah Anggeraini Hasri (Escalate : Economics and Business Journal, 2026)
In Sumbawa Regency, the creative industry is minimal (0.8% of MSMEs) amid abundant iron waste following the 2022 MXGP boosting tourism, prompting Samalewa Recycled Iron Craft—initiated by Sumbawa University of Technology students—to transform iron waste into unique crafts (wall hangings, miniatures) for a circular economy. This qualitative descriptive study aims to describe the business model, analyze digital marketing strategies, and formulate e-commerce-based development strategies; population comprises student teams and campus stakeholders with purposive sampling; instruments include internal-secondary document analysis, techniques employ Business Model Canvas (BMC) and SWOT. Results reveal an innovative BMC (affordable recycled materials, custom designs), marketing via social media-marketplaces-content; SWOT identifies low-cost strengths, limited capacity weaknesses, eco-trend opportunities, import threats. The study concludes with recommendations for e-commerce optimization, digital branding, and payment integration to enable national expansion.